Adaptive sink mobility for energy-efficient data collection in grid-based wireless sensor networks. (2018) - Messai, Sarra; Aliouat, Zibouda; Seba, Hamida; Boukerram, Abdallah
Many recent studies show that sink mobility in wireless sensor networks (WSNs) preserves the energy of the sensors for a longer network lifetime. These approaches require generally a logical organisation of the network within clusters, such as a grid. However, constructing such a grid is costly and requires several rounds of messages exchanged between sensors which outbalance the benefits of the approach. To tackle this drawback, we propose an energy-based cell-head (CH) selection combined with a sink mobility algorithm to minimise energy consumption of sensor nodes and optimise data collection. The proposed approach is termed EASY for energy-aware sink mobility. Experimentation results confirm that our solution offers better performance compared to existing approaches.